Fetal dystocia and estimation of fetal age in Sheep - singh, laishram kipjen; Singh, Umed; Singh, Prem (The Indian Journal of Animal Reproduction, 2023)
A non–descript primiparous sheep of unknown gestation was presented with a history of difficulty in parturition and  foul smell bloody vaginal discharge. Vaginal examination revealed dead fetus in anterior longitudinal presentation with  carpal flexion retained in the birth canal. Based on the gynaeco-clinical examination, the case was diagnosed as dystocia  due to carpal flexion. Further, the fetal age of the lamb was calculated using the formula given by Richardson (1980) as  130 days. The present case study deals with the successful management of dystocia due to carpal flexion and its estimation  of fetal age in a non-descript sheep.
Keywords: Crown-anus length; Dystocia; Carpal flexion; Lamb